Examining the reliability of the 100 point functional movement screen scoring system - Everard, E.; Harrison, A.; Lyons, M.; Elwell, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The Functional Movement Screen (FMS) is one of the most widely used movement screens in both research and practical settings. The FMS comprises of seven tests that are traditionally graded from 0 to 3, providing a composite score out of 21. A 100 point scoring system has been developed in order to improve the ability of the FMS to detect variations in movement quality between participants. The reliability of the 100 point system has yet to be fully investigated, with currently no published studies reporting intra-rater reliability and only one study examining the inter-rater reliability of the 100 point scoring system. Therefore, the primary aim of this investigation was to examine both inter- and intra-rater reliability of the 100 point FMS scoring system using two chartered physiotherapists who are both certified and experienced with the FMS (>1000 screens conducted). Methods: 110 physically active collegiate males (mean ± SD 21.43±3.2 years; body mass= 77.27±8.7kg; height=177.5±6.8cm) were videotaped undertaking the seven FMS tests: Squat, lunge, hurdle, rotary stability, press up, active straight leg raise (ASLR) and shoulder mobility (Shld). Thirty participants were randomly chosen and their videos were re-scored 6 weeks later by the second rater and again by the first rater. Inter- and intra-rater reliability of both the final scores and component tests were analysed using Intra-Class Coefficients (ICC) and kappa statistics with associated 95% Confidence Intervals (CI) respectively. Results: Inter- and intra-rater ICC values for the total scores were .97 (.95-.98) and .98 (.97-.99) for the 100 point and .98 (.96-.99) and .99 (.96-.99) for the 21 point scoring system, indicating that both scales had almost perfect inter- and intra-rater reliability. All the component tests using both scoring systems had between perfect and substantial agreement for both inter- and intrarater reliability. For intra-rater reliability, the 100 point scale had seven measures that were perfect or almost perfect (Shld, ASLR, squat, right rotary stability) and five measures had substantial agreement (lunge, left rotary stability, hurdle). For inter-rater reliability, the 100 point scale had 10 of the tests that were either perfect or near-perfect agreement and 2 (Right Lunge and Hurdle) with substantial agreement. Every measure using the 21 point scale had perfect or almost perfect inter- and intra-rater agreement with the exception of the rotary stability test, which had substantial agreement. Conclusion: Both the 100 point and 21 point scoring systems had substantial to excellent levels of inter- and intra-rater reliability for both the total score and component scores. Experienced practitioners should feel confident using the 100 point scoring system, which may help distinguish athletes of different movement abilities more effectively than the 21 point scoring system.